Identification and Molecular Investigation of Diplostomum in Capoeta umbla Caught from Freshwater Sources, Turkey - Barata, Sibel Doğan; Dörücü, Mustafa; Gürses, Murad (Central Fisheries Research Inst, 2022)
In this study, identification of the cytochrome c oxidase subunit I (COI) gene region in mitochondrial DNA of the Diplostomum specimens, which are parasitic in the eyes of Capoeta umbla fish naturally distributed in Karakaya Dam Lake, Keban Dam Lake and Lake Hazar, (Elazığ province) was performed. A total of 8 haplotypes were determined using sequence analysis of the mtCOI gene region and phylogenetic trees were constructed by determining the genetic distance based on these haplotypes by the Maximum Likelihood (ML), Neighbor Joining (NJ), Minimum Evolution (ME) and Bayes methods. As a result, the lowest genetic distance was 0,00209 and the highest genetic distance was 0,01264. Phylogenetic analysis revealed a closer relationship between haplotype 3 and haplotype 4. It has been evaluated that all the samples studied belong to Diplostomum spathaceum and that the parasite may have been spread by the main hosts between study sites. © 2022, Central Fisheries Research Inst. All rights reserved.
Keywords: Capoeta umbla; COI; Diplostomum; PCR; Phylogenetic